1976
DOI: 10.1007/bf00507347
|View full text |Cite
|
Sign up to set email alerts
|

Spastic paresis after 6-aminonicotinamide: Metabolic disorders in the spinal cord and electromyographically recorded changes in the hind limbs of rats

Abstract: In rats the application of 10 mg/kg 6-amino-nicotinamide (6-AN) leads to an accumulation of 6-phosphogluconate, by inhibition of 6-phosphogluconate dehydrogenase in the pentose phosphate pathway, in the cells of the spinal cord. The accumulation reaches its maximum after 18-24 h. It seems that there exists a relationship between the accumulation of 6-phosphogluconate and the lesion of the neuroglia, which is found in electron microscopic studies. Symptoms of a spastic paresis only develop later when the spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…TN administration as a single dose in human xenograft mouse models produced a promising result comparable to that of NADK downregulation (50%) with shRNA [ 73 ]. Another NAD + analog, 6-amino nicotinamide, showed promising pre-clinical anti-cancer activity but was associated with neurological toxicity [ 80 ]. The neurotoxicity of 6-amino nicotinamide was ascribed to its ability to block the pentose phosphate pathway via phosphogluconate dehydrogenase inhibition [ 81 ] and inhibit NADK2 phosphorylation [ 79 ].…”
Section: Nad Analog As Potential Nadk Inhibitorsmentioning
confidence: 99%
“…TN administration as a single dose in human xenograft mouse models produced a promising result comparable to that of NADK downregulation (50%) with shRNA [ 73 ]. Another NAD + analog, 6-amino nicotinamide, showed promising pre-clinical anti-cancer activity but was associated with neurological toxicity [ 80 ]. The neurotoxicity of 6-amino nicotinamide was ascribed to its ability to block the pentose phosphate pathway via phosphogluconate dehydrogenase inhibition [ 81 ] and inhibit NADK2 phosphorylation [ 79 ].…”
Section: Nad Analog As Potential Nadk Inhibitorsmentioning
confidence: 99%
“…The only NADK inhibitor that has been tested in the clinic is 6-amino nicotinamide, which had shown promising preclinical anticancer activity, although animal studies showed that neurologic toxicity was dose limiting (41). Unfortunately, neurotoxicity prevented dose escalation, and minimal activity was seen at the maximum tolerated dose in clinical trials (42).…”
Section: Thionicotinamidementioning
confidence: 99%